Rebuilding futures enhancing rehabilitation for Children in Conflict with the Law (CICL) in Bahay Pag-Asa Centers through the development of a salutogenic park design - Mentoy, Valerie I. (College of Architecture, University of the Philippines Diliman, 2025)
The prevalence of poverty in the Philippines continues to be a catalyst for various social issues that affect the most vulnerable and marginalized part of the population. One of these is the increasing cases of juvenile delinquency among the youth, who are referred to as Children in Conflict with the Law (CICL). Under R.A. 9344 and R.A. 10630, the CICL are granted the rights to undergo rehabilitation for their criminal offenses, instead of being subjected to court proceedings. This rehabilitation is implemented within a Bahay Pag-Asa (BPA), which pertains to a transformational institution that provides CICL with intensive intervention programs conducted by a multidisciplinary team of professionals. Despite the laws that require a set of standards for the establishment of these BPAs, many of the youth reformation facilities in the country remain incompliant and thus, inadequate in giving proper rehabilitation for the CICL. Among the 114 operational halfway houses, only 31 received accreditation from the Juvenile Justice and Welfare Council (JJWC) for meeting the minimum requirements. For this reason, the study aims to propose open parks near the vicinity of multiple BPA centers within the National Capital Region (NCR), which recorded the highest reported CICL incidents in recent years, in order to support the facilities and allow the provision of a more diverse set of programs and activities. This will mostly utilize a qualitative methodology comprised of site selection criteria, site suitability matrix, key informant interviews, focus group discussions and document review. It will also employ quantitative data through statistical reports. The study seeks to serve as guide for the utilization of landscapes in the rehabilitation of the CICL by designing a salutogenic open park. This incorporation of restorative landscapes in the BPAs supports the CICL by providing a more conducive environment which will aid in their eventual reintegration into society.